Note from the Editor-in-Chief: A Second Farewell. Issue 3 (2nd September 2019) - Kuchuck, Steven
Abstract : In my final note as Editor-in-Chief of the journal, I express my appreciation for the talented staff and make an announcement about the future leadership of the journal.